2006
DOI: 10.1111/j.1439-0426.2006.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical distribution of digestive enzymes in intestine of goldline, Sarpa salpa L. 1758

Abstract: Histochemical localization of non-specific esterase, alkaline and acid phosphatase in the intestine of free-living goldline (Sarpa salpa L. 1758) was investigated. Fish were caught in the vicinity of the town of Zadar (Adriatic Sea, Croatia), and samples of three parts of the intestine proper (anterior, middle and posterior) as well as the rectum were used for presentation of non-specific esterases, alkaline phosphatase and acid phosphatase. Non-specific esterase activity was found in the cytoplasm and brush b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 43 publications
6
27
0
1
Order By: Relevance
“…These observations suggest that the enterocytes of the anterior portion of the intestine are involved in lipid absorption. This suggestion is in accordance with that of Stroband and Debets (1978), in Ctenopharyngodon idella, Anderson (1986), in Girella tricuspidata, Deplano et al (1989), in Dicentrarchus labrax, Olsen et al (1999), in Salvelinus alpinus, Gallagher et al (2001), in Lagodon rhomboids, Caballero et al (2003), in Sparus aurata, Kozarić et al (2004), in Merluccius merluccius, and Carrassón et al (2006), in Dentex dentex. Moreover, Fontagné et al (1998), in Cyprinus carpio, stated that the intestinal fat droplets can be interpreted as a temporary storage form of the re-esterified fatty acids.…”
Section: In Esox Lucius and Silurus Glanis Andsupporting
confidence: 75%
“…These observations suggest that the enterocytes of the anterior portion of the intestine are involved in lipid absorption. This suggestion is in accordance with that of Stroband and Debets (1978), in Ctenopharyngodon idella, Anderson (1986), in Girella tricuspidata, Deplano et al (1989), in Dicentrarchus labrax, Olsen et al (1999), in Salvelinus alpinus, Gallagher et al (2001), in Lagodon rhomboids, Caballero et al (2003), in Sparus aurata, Kozarić et al (2004), in Merluccius merluccius, and Carrassón et al (2006), in Dentex dentex. Moreover, Fontagné et al (1998), in Cyprinus carpio, stated that the intestinal fat droplets can be interpreted as a temporary storage form of the re-esterified fatty acids.…”
Section: In Esox Lucius and Silurus Glanis Andsupporting
confidence: 75%
“…Diverse enzymes involved in digestive and absorptive processes have been reported in a variety of adult fish (Kuz'mina and Gelman 1997;Cahu et al 2000;Kozarić et al 2004;Kozarić et al 2006). Distribution intensity of digestive enzymes across the gastrointestinal tract varies with feeding habits and intestinal morphology (Kolkovski 2001;Gawlicka et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…The two-layered muscularis externa of the European hake oesophagus is made of striated muscular tissue. The activity of enzymes such as non-specific esterase, acid and alkaline phosphatase, was found to be weak to moderate in the hake's oesophagus (Kozarić et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…When treated with Alcian blue/PAS, it seems that the intestinal goblet cells contain acidic mucins. Kozarić et al (2004) described that in the European hake intestinal intraepithelial goblet cells showed no enzymatic activity, but dispersed granular enzymatic activity was observed in the connective tissue of lamina propria. The results reported by Ferrando et al (2006) showed that the morphology of the mucosal folds of the Liza aurata intestine, as well as the quality and quantity of the mucous from the intestinal goblet cells, bear a relationship with environmental pollution.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation